The Personal Before and After the Political: Case Study of a Dialogue Methodology for Crisis - Dini, Elena (The ecumenical review, 2024)
The authors of this article co-facilitated a dialogue workshop for Jewish, Christian, and Muslim communal leaders and academics in Cairo as part of the GINGKO Interfaith Fellowship Retreat in September 2024. The Interfaith Dialogue in Times of Crisis workshop guided the participants through a series of exercises, culminating in reflections on how to move forward. In preparation, the authors held their own retreat, speaking openly and personally about how they had experienced the events of 7 October 2023 and their immediate aftermath, seeking mutual understanding and strengthening their deep relationships. We modelled this work for the group at the workshop in Cairo. We will share several methodological successes from that retreat, as well as reflecting on some structural challenges and representational issues that shifted our focus on the final day of the retreat.